Michael Vey: The Colony - Book 10 - Evans, Richard Paul (New York : Mercury Ink/Simon Pulse, 2024)
"After saving Tara and Jack--and losing a few of their own--in a dramatic battle in the Peruvian jungle against the Elgen offshoot the Chasqui, the Electroclan has returned to the US to regroup. But their downtime is brief, as Abi--who was abducted from outside her college dorm--is still missing. Piecing together what few clues they have from video footage of the abduction as well as some additional information from Grace--whose consciousness has broken free of her physical body and connected with worldwide intelligence--they determine that she is being held somewhere in Peru by the leader of a group of other electrics known as the Colony"--
Keywords: Vey, Michael -- Juvenile fiction; Vey, Michael -- Fiction; Friendship in adolescence -- Juvenile fiction; Missing persons -- Juvenile fiction; Electricity -- Juvenile fiction; Tourette syndrome in adolescence -- Juvenile fiction; Friendship -- Fiction; Missing persons -- Fiction; Electricity -- Fiction; Tourette syndrome -- Fiction; Science fiction; Peru -- Juvenile fiction; Peru -- Fiction; Juvenile fiction